2015
DOI: 10.1097/aog.0000000000001094
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Use of Long-Acting Reversible Contraceptive Methods Among U.S. Women, 2009–2012

Abstract: OBJECTIVE To examine current levels, current correlates of, and changes in long-acting reversible contraceptive (LARC) use, including intrauterine devices and implants, among females aged 15–44 years using contraception between 2008–2010 and 2011–2013 with specific attention to associations between race, income, and age and their LARC use. METHODS We analyzed data from two rounds of the National Survey of Family Growth, nationally representative samples of females aged 15–44 years, consisting of 6,428 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(168 citation statements)
references
References 18 publications
11
149
3
5
Order By: Relevance
“…Consistent with Hu’s finding, despite the increasing need for LARC methods in China, there was a decreasing use of IUDs 16. In the USA, data from National Survey of Family Growth showed that LARC use increased 18.0% per year among postpartum women 17. The reason for the decreasing use of IUDs in China could be the relaxed reproductive policy which probably encourages individuals to have higher preference for short-term methods 5…”
Section: Discussionmentioning
confidence: 69%
“…Consistent with Hu’s finding, despite the increasing need for LARC methods in China, there was a decreasing use of IUDs 16. In the USA, data from National Survey of Family Growth showed that LARC use increased 18.0% per year among postpartum women 17. The reason for the decreasing use of IUDs in China could be the relaxed reproductive policy which probably encourages individuals to have higher preference for short-term methods 5…”
Section: Discussionmentioning
confidence: 69%
“…While a study in Uganda showed the current use of LARC was 31.7%, [14], in Ghana 71% [10], in US 11.6% [16], in Western Ethiopia 17.6% [17] and a study in France showed the current LARC use was much lower (6.6% ) of which 2.6% were using the implant, 1.5% had a copper IUCD [11]. Variation among these studies might be due to the difference in sampling procedures, study designs, setting and time of study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantages, use of LARCs remains relatively small. Thus this study tries to find out the prevalence, reasons, perception and factors contributing to utilization of LARC by FP clients [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Long-acting reversible contraceptive (LARC) methods, including the contraceptive implant, are highly effective 2. Use of these methods is increasing but overall is underutilised, especially among young women 3 4…”
Section: Introductionmentioning
confidence: 99%